2016
DOI: 10.1186/s12889-016-3789-z
|View full text |Cite
|
Sign up to set email alerts
|

Urban–rural and geographic differences in overweight and obesity in four sub-Saharan African adult populations: a multi-country cross-sectional study

Abstract: BackgroundOverweight and obesity are on the rise in developing countries including sub-Saharan Africa. We undertook a four-country survey to show the collective burden of these health conditions as they occur currently in sub-Saharan Africa and to determine the differences between urban and rural populations and other socio-economic factors.MethodsParticipants were nurses in two hospitals in Nigeria (200), school teachers in South Africa (489) and Tanzania (229), and village residents in one peri-urban (297) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
95
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 41 publications
19
95
3
Order By: Relevance
“…Other studies in urban Burkina Faso or hospital (outpatients) settings reported that women were more overweight and obese than men [12,2225]. In their study in four sub-Saharan countries (Nigeria, South Africa, Tanzania, Uganda) Ajayi et al also reported the gender difference in favour of women [11]. Nonetheless, the overall prevalence of overweight and obesity in our study is similar to those reported in the STEPS surveys for rural Burkina Faso (overweight: 8.5% vs 9.4% and obesity: 1.8% vs 1.9%).…”
Section: Discussionmentioning
confidence: 94%
“…Other studies in urban Burkina Faso or hospital (outpatients) settings reported that women were more overweight and obese than men [12,2225]. In their study in four sub-Saharan countries (Nigeria, South Africa, Tanzania, Uganda) Ajayi et al also reported the gender difference in favour of women [11]. Nonetheless, the overall prevalence of overweight and obesity in our study is similar to those reported in the STEPS surveys for rural Burkina Faso (overweight: 8.5% vs 9.4% and obesity: 1.8% vs 1.9%).…”
Section: Discussionmentioning
confidence: 94%
“…Other sex-specific associations included that with marital status, as this study has shown that men who were married had a higher BMI than their unmarried counterparts, while married women had a lower BMI than unmarried women. A multi-country study of four SSA countries has shown inconsistent associations between marital status and BMI in the various study settings [35] and suggests the possible influence of population-specific cultural beliefs around body size and marriage.…”
Section: Discussionmentioning
confidence: 99%
“…Reported lifestyle factors include alcohol consumption, smoking [18,19] and physical inactivity [20]. The role of genetic factors in determining BMI has also been extensively reported in the literature [21,22]. Several cross-sectional and longitudinal studies in non-African countries have also observed a positive association between BMI and pesticide exposure [2327].…”
Section: Introductionmentioning
confidence: 99%